Metabolomics Study on the Mechanism of Junfang Tea in Regulating Glucose and Lipid Metabolism - Zhao, Jingyi; Li, Yanyan; Li, Xue; Zhao, Jianhui; Qiu, Xiangjun (International Journal of Public Health and Medical Research, 2024)
Objective: This study aims to explore the regulatory effects and potential mechanisms of Junfang tea extract on metabolic disorders induced by a high-sugar, high-fat diet. Methods: A high-sugar, high-fat mouse model was established, and 220 healthy male mice were randomly divided into seven groups: normal control group (NC), model control group (MC), positive control group (PC), and four Junfang tea extract groups (DYA, DYB, DYC, DYD). The NC and PC groups consisted of 35 mice each, while the other groups had 30 mice each. The NC group was fed a standard diet, while the other groups were fed a high-sugar, high-fat diet for 8 weeks to induce the model. Starting from the 9th week, the observation groups were administered different doses of Junfang tea extract by gavage, while the PC group received metformin and lovastatin as positive controls. In the 15th week, blood samples were collected, and serum was separated for the measurement of glucose (Glu), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein (TP), albumin (ALB), urea, and creatinine levels. Results: Tea polyphenols and catechins are the main active components in Junfang tea, which regulate several metabolic pathways, including fatty acid oxidation, fat synthesis, and glucose metabolism, by modulating the AMPK, PPAR, and SREBP signaling pathways. Differential metabolite analysis showed that the abundance of Sinapoylhexoside and other metabolites was significantly higher in the NC group than in the MC group, suggesting its potential role in maintaining metabolic balance. Pathway Impact analysis revealed that Junfang tea significantly alleviated metabolic disorders induced by a high-sugar, high-fat diet through the regulation of key signaling pathways, such as AKT, mTOR, NF-κB, and JNK. Multi-group comparison analysis indicated that the metabolic state of group D showed noticeable improvement, approaching that of the normal control group (NC), although it did not fully return to normal levels. Conclusion: Junfang tea extract significantly reduced blood glucose and lipid levels in high-sugar, high-fat model mice and regulated glucose and lipid metabolism through multiple metabolic pathways, demonstrating its potential value in improving metabolic diseases.